Diagnostic Imaging of Musculoskeletal Diseases 2009
DOI: 10.1007/978-1-59745-355-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Diseases of Bone and Adjacent Soft Tissues

Abstract: The blood circulation of bone may be affected by a variety of insults, involving the arterial, capillary, sinusoidal or venous networks. Blood flow impedance may be due to mechanisms such as intraluminal obstruction, vascular compression or physical disruption of the vessel. In circulatory diseases of bone, imaging aims to demonstrate the reparative host response. Avascular necrosis (AVN) is a lesion in which an early diagnosis is vital in order that the appropriate management can be undertaken, with the femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
1
0
0
Order By: Relevance
“…The radiographic hallmark of osteochondritis was increased bone density in an otherwise normal joint. Established osteochondritis is seen as collapse of the articular surface and fragmentation [13]. Our results showed that Freiberg disease occur in older children (14-16 years old), this agreed with a study [14] who said that the time of onset of Freiberg's disease was 14-18 years old, presented with pain and swelling of second metatarsal head.…”
Section: Discussionsupporting
confidence: 91%
“…The radiographic hallmark of osteochondritis was increased bone density in an otherwise normal joint. Established osteochondritis is seen as collapse of the articular surface and fragmentation [13]. Our results showed that Freiberg disease occur in older children (14-16 years old), this agreed with a study [14] who said that the time of onset of Freiberg's disease was 14-18 years old, presented with pain and swelling of second metatarsal head.…”
Section: Discussionsupporting
confidence: 91%